2022
DOI: 10.1111/adb.13159
|View full text |Cite
|
Sign up to set email alerts
|

People with tobacco use disorder exhibit more prefrontal activity during preparatory control but reduced anterior cingulate activity during reactive control

Abstract: Reduced inhibitory control and a hypersensitivity to reward are key deficits in drug dependents; however, they tend to be studied in isolation. Here, we seek to understand the neural processes underlying control over reward and how this is different in people with a tobacco use disorder (pTUD). A novel variant of the monetary incentive delay task was performed by pTUD (n = 20) and non-smokers (n = 20), where we added a stop-signal component such that participants had to inhibit prepotent responses to earn a la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…disinhibition previously observed following 3-72 nicotine withdrawal across a range of inhibitory control tasks (Mendrek et al, 2006;Dawkins et al, 2007;Harrison et al, 2009;Charles-Walsh et al, 2014;Tsaur et al, 2015;Kalhan et al, 2022). The present study is the first to demonstrate that short-term withdrawal can also increase risky decision-making on the IST.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…disinhibition previously observed following 3-72 nicotine withdrawal across a range of inhibitory control tasks (Mendrek et al, 2006;Dawkins et al, 2007;Harrison et al, 2009;Charles-Walsh et al, 2014;Tsaur et al, 2015;Kalhan et al, 2022). The present study is the first to demonstrate that short-term withdrawal can also increase risky decision-making on the IST.…”
Section: Discussionsupporting
confidence: 66%
“…In comparison to HSs, 12-h deprived smokers displayed significantly poorer inhibitory control and heightened reflection impulsivity, yet significantly lower levels of impulsive choice. This supports the heightened disinhibition previously observed following 3–72 h of nicotine withdrawal across a range of inhibitory control tasks (Mendrek et al ., 2006; Dawkins et al ., 2007; Harrison et al ., 2009; Charles-Walsh et al ., 2014; Tsaur et al ., 2015; Kalhan et al ., 2022). The present study is the first to demonstrate that short-term withdrawal can also increase risky decision-making on the IST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported reduced activity in the IFG as neural markers of substance abuse and ADHD [4850]. However, increased activity in the IFG has also been reported in individuals with tobacco use disorder [51], and increased IFG activity suggests that more preparatory effort is required for successful inhibition [52].…”
Section: Discussionmentioning
confidence: 99%